AB0493 Anti-TNFα treatment is associated with increased liver stiffness in HBV occult carrier patients. (23rd January 2014) - Tirri, R.; Stornaiuolo, G.; Sessa, P.; Orefice, M.; Brancaccio, G.; Valentini, G.; Gaeta, G.B.
Abstract : Background: HBV occult carriers (i.e HBsAg-/HBcAb+) are at risk for viral reactivation under immunosuppressive treatment for cancer and transplantation. Even if rarely, HBV reactivation has been also reported in occult HBV infection patients with Rheumatoid Arthritis (RA) or Spondyloarthritis (SA) undergoing anti TNFα treatment. No data are available on the influence of such treatment on liver architecture. Objectives: This study was devoted to address this topic. Methods: Liver fibrosis, as evaluated by Transient Elastografy (TE), was investigated in 73 patients with RA or SA undergoing anti TNFα treatment. Out of them, 6 were HBcAb+/HBsAb-; 33 HBcAb +/HBsAb+; in 2 HBcAb+, HBsAb was not available; 32 were HBcAb-. The patients were observed for a mean period of 43, 9±26, 3 months, during which ALT was measured every 4 weeks. HBV-DNA was evaluated if ALT increased more than 2 x upper normal value in 2 consecutive determinations. For each patient, 10 measurement of liver stiffness were performed and reported as average kPa value. A cut off value of 7, 3 was assumed to denote significant fibrosis. BMI was calculated in all patients. Results: Out of the seventy three patients (37F, aged 56, 9±11, 3) investigated, 18 were treated with Infliximab (IFX), 24 with Etanercept (ETA), 24 with Adalimumab (ADA) and 7 with Golimumab (GOL); 20 patients were also treated with Methotrexate (MTX), 10 with Leflunomide (LFN), 26 with Sulfasalazine (SSZ) and 12 with Prednisone (PDN) (<7.5 mg/die). There was no differences in age, gender, BMI, duration of treatment, MTX or other DMARDs use, between HBcAb+ and HBcAb- patients (p>0.05). No case of HBV reactivation was recorded. A stiffness value >7, 3 KPa was detected in 10/41 (24, 4%) anti HBc + patients vs 1/32 (3%) patients anti HBc - (p=0.02). Conclusions: In our series the presence of anti-HBc antibodies identifies a subgroup of patients with liver damage, despite normal ALT values. This suggests that anti-TNFα therapy might promote liver fibrosis in occult HBV carriers or that some anti-HBc positive patients had a past-history of liver damage due to previous active HBV infection. These results await to be assessed in a longitudinal study. References: Calabrese LH, Zein NN, Vassilopoulos. Hepatitis B virus (HBV) with immunosuppressive therapy in rheumatic diseases: assessment and preventive strategies. Ann Rheum Dis 2006;65;983-989. Caporali R et al. Safety of tumor necrosis factor α blockers in hepatitis B virus occult carriers (hepatitis B surface antigen negative/anti-hepatitis B core antigen positive) with rheumatic diseases. Arthritis Care Res. 2010, 749-754. Castera L, Forns X, Alberti A. Non-invasive evaluation of liver fibrosis using transient elastography. J Hepatol. 2008 May;48(5):835-47. Bonino F, Arena U, Brunetto MR, Coco B, Fraquelli M, Oliveri F, Pinzani M, Prati D, Rigamonti C, Vizzuti F; Liver Stiffness Study Group "Elastica" of the Italian Association for the Study of the Liver. Liver stiffness, a non-invasive marker of liver disease: a core study group report. Antivir Ther. 2010;15 Suppl 3:69-78. Disclosure of Interest: None Declared